MAKING OF THE CD VIDEO APPLICATIONS WITHOUT DELAY WITH ADOBE PREMIERE 6.0 - Adi Swastono; Hariyanto SKom, MMSI Hariyanto SKom, MMSI (Jurnal Sistem Informasi, 2004)
The rapid development of the multimedia world and the competition becomes moreintense also because they are supported by the development of an increasinglysophisticated information technology lately. So that at present no longer need tomanually process the video with the price of equipment is difficult to reach thepublic. But there are a few things to note in this video processing to achievemaximum results and satisfaction. Adobe Premiere 6.0 software's presence was morehelpful in processing the video for a fa